Epidermolysis bullosa acquisita - V. V. Chikin; L. F. Znamenskaya; M. A. Nefedova; V. A. Charikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes present-day information on the pathogenesis, clinical picture, treatment and differential diagnostics of epidermolysis bullosa acquisita, an autoimmune skin disease caused by the production of anti-Type VII collagen autoantibodies and manifested mainly by subepidermal blisters and erosions. The authors present the results of a case study of a rare form of epidermolysis bullosa - epidermolysis bullosa acquisita in a male patient aged 53. A combined therapy with peroral prednisolone and subcutaneous injections of methotrexate had a positive effect in the form of epithelialization of most of the erosions.